BSCI-17. YOUNG AGE PROMOTES BREAST CANCER METASTASIS TO THE BRAIN. (12th August 2019) - Wu, Alex; Gossa, Selam; Chung, Monika; Dolan, Emma; Yang, Howard; Isanogle, Kristine; Robinson, Christina; Difilippantonio, Simone; Gril, Brunilde; Lee, Maxwell; McGavern, Dorian; Wakefield, Lalage; et al.
Abstract: Younger women (< 40 years old) diagnosed with breast cancer often have a poorer outcome and a higher risk of developing brain metastases compared to women diagnosed at an older age. Multi-variate analyses have shown that even after accounting for differences in primary tumor characteristics, young age is still an independent predictor of poorer outcome. We therefore hypothesize that rather than intrinsic tumor properties, age-related changes to microenvironmental factors can affect breast cancer metastasis. To test this hypothesis, human and mouse breast cancer cells were injected into young (< 6 month) and old (> 13 month) mice and metastatic tumor burden was quantified. Young mice injected with brain-seeking breast cancer cells (MDA-MB-231BR, 4T1-BR, and 99LN-BrM) developed significantly more brain metastases compared to their older counterparts. In contrast, age had no effect on lung metastatic tumor burden in five breast cancer models. The effect of age is organ-specific, and the young brain is more permissive for breast cancer metastasis. To gain mechanistic insight, the transcriptome of young and old mouse brains were analyzed by RNAseq, the metastatic microenvironment was analyzed by laser capture microdissection and mass spectrometry, immune populations have been identified by flow cytometry, and functional immune contributions analyzed by immunodepleting antibodies. Multiple brain immune subsets were altered with age. In vivo depletion experiments showed no significant contribution of CD4+ T-cells and GR1+ myeloid cells to baseline brain metastatic colonization. A subpopulation of microglia in aged metastatic brains had a high side-scatter profile, which is consistent with published reports that aged microglia are in a "pro-inflammatory" state. Depletion of microglia reduced baseline brain metastatic colonization by 50% and experiments are underway to determine their contribution to an age effect.